Legal regulation of providing psychiatric care in Ukraine: problems and prospects - Anishchenko, M. A.; Hamburh, L. S.; Krasnokutskyi, O. V.; Glazunov, V. V.; Davidov, P. G.; Аніщенко, Михайло Анатолійович; Гамбург, Леонід Самойлович (My University, 2022)
The concept of “man” expresses the biosocial nature of the individual, who, as a result of evolution,united animal-biological and social principles, which determined his features in the biological form of the movement of matter and provided access to the highest social level of such movement. At the same time, the social principles of a person are his essence, manifested through a personality that is formed only in a social environment and characterizes a person as the bearer of the entire totality of social relations. The main tool for the formation of personality is the ability of the human brain and the entire nervous system to reflect objective reality in social practice in the form of subjective images, which leads to the formation and development of abstract thinking. The latter, together with articulate speech and the ability to work to transform objects of primary nature into a secondary one, constitutes the substantive basis of the personality, forming an individual consciousness. Therefore, one of the determining factors of social wellbeing and progress is the state of consciousness of individuals, which underlies the consciousness of social classes, groups and strata, as well as the mass consciousness of the people.